„Judenfrage”. Retoryczny obraz propagandy antysemickiej w III Rzeszy (na przykładzie publicznych wypowiedzi Adolfa Hitlera i innych polityków NSDAP w latach 1933–1945) - Grzegorzewski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article is a rhetorical analysis of speeches by the NSDAP politicians, dedicated to German anti-Semitic politics in the Third Reich. The purpose of this article is to characterise the rhetoric of anti-Semitic propaganda and answer the question what the influence of this rhetoric on the German society was. The most interesting question is the way of justifying this criminal politics by the Nazis. The present author bases his research on the original German speeches by the most known NSDAP politicians, transmitted in a German radio station, Der Grossdeutsche Rundfunk.